Prevalence of Dental Erosion in a Group of Schoolchildren from Benghazi, Libya - Ahmed Ali Musrati; Huew Rasmia; Fowziya Ali; Khadija Herwis; Fathiya Mohamed (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Aims: Despite the growing concern that the prevalence of dental erosion has increased amongst children, the data on its prevalence is still scarce in Libya. Therefore, this study aimed to measure the prevalence of dental erosion and examine gender differences in relation to its prevalence in a group of schoolchildren in Benghazi, Libya. Methods: A cross-sectional observational study was conducted in Benghazi. A random sample of 12 year-old schoolchildren (n=180; 92 boys and 88 girls) attending elementary schools in Benghazi were dentally screened for erosion using UK National Diet and Nutrition Survey (NDNS Criteria). Results: The prevalence of dental erosion was 38.9%. A higher experience of erosion was observed amongst girls (40.9%) than boys (37%), this difference was not statistically significant (p=0.647). Conclusions: In the present study, the relatively high proportion of children in Benghazi, Libya affected by dental erosion emphasizes the importance of preventive measures needed to control the erosive process, before more invasive treatments become a necessity to restore eroded teeth.